Prevalence of Absence of Palmaris Longus Tendon in Nepalese Population - Sharma, Nitasha; Parajuli, Bikash; Pandey, Niraj; Shah, Ram Prakash (Journal of Universal College of Medical Sciences, 2019)
INTRODUCTION: The palmaris longus (PL) is a tendinous superficial flexor of forearm. It basically, anchor skin and fascia of hand resist the horizontal shear force in distal direction. It also helps in tightening of palmar aponeurosis. Along with other flexor muscle it also helps in flexion of wrist joint. The incidence of absence of palmaris longus is in great variation from 1.5 to 63.9%. Its variation of absence has attracted many researchers globally. The aim of the present study is to know occurrence of absence of PL in Nepalese population. MATERIAL AND METHODS: This is a cross sectional descriptive observational study conducted among 270 medical students (MBBS, BDS) at Universal College of Medical Science, Bhairawaha in year the 2018-2019. Ethical approval for study was taken from institutional review committee (IRC). Four tests-Schaeffer's Test, Thompson's Fist, Mishra's Test and Puspa Kumar's two finger sign were used to see the absence/presence of Palmaris longus. A semi-structured proforma was used to collect the data. RESULTS: Out of 270 students, there were 145 (53.7%) females and 125 (46.3%) males. Age of the subject range from 19-23 years with a mean age of 19.91 years. The overall absence of palmaris longus was seen in 40 students (14.8%) which included 18 males (14.4%) and 22 females (15.2%). Bilateral absence of palmaris longus was seen in 10 students (3.7%) whereas unilateral absence of palmaris longus was seen 14 males (11.2%) and 16 females (11.03%). CONCLUSION: This present study concluded that overall absence of palmaris longus was seen in 14.8% subjects. Gender wise distribution showed that 14.4% males and 15.2% had the absence of palmaris longus. Thus, sound knowledge about this variation is important in planning graft surgeries.